The dynamic growth and standing stock of Acacia decurrens following the 2006 eruption in Gunung Merapi National Park, Java, Indonesia - Suryanto, Priyono; Hamzah, Mohd Zaki; Mohamed, Azmy; Alias, Mohamad Azani (Canadian Center of Science and Education, 2010)
Following the 2006 eruption in Mount Merapi, Indonesia, it is important to assess the dynamic growth and potential standing stock of Acacia decurrens as a woodfuel for the local community surrounding in the southern of Gunung Merapi National Park. Five plots (P1, P2, P3, P4 and P5), were established. This study carried out in May 2008. During the period of 18 months, the performance of A.decurrens was examined: recruitment, mortality, survival, diameter, height, density, basal area, volume and relative rate change. The highest average diameter and height of A.decurrens were 14.22±1.85cm and 5.97±0.66m, respectively. Standing stock was based on the highest average of the basal area (i.e. 72.067±18.51 m2/ha) and volume (i.e. 184.44±24.59 m3/ha). The results of this study were important information in supporting the Merapi lava tour and the standing stock of A. decurrens, which promises the local community with a schematic compatible management for GMNP.